'What do you see now?': lessons learned while integrating a virtual reality application in ambulatory care of a pediatric surgery. Issue 3 (17th February 2023) - Flegel, Nadine; Mentler, Tilo
ABSTRACT: In many medical contexts, virtual reality (VR) applications are associated with high hopes for improved forms of care. In order for these hopes to be fulfilled not only in controlled (laboratory) studies, possibly accompanied by technicians, but also in everyday clinical practice, applications must be suitable for the users on the one hand and efficiently integrated into the organisational processes on the other. While the first aspect has already been widely studied in terms of VR-related user interface and interaction design, there are fewer references and recommendations on the second one. These are given in this contribution. They are based on findings of applying human-centred design methods (contextual inquiry, work models, focus group) during the integration of a VR application in ambulatory care of children and adolescents after bone fractures. Finally, transferability of the recommendations to other contexts, including beyond clinical scenarios, is discussed.